The peninsula question : a chronicle of the second Korean nuclear crisis - Funabashi, Yōichi, 1944- (Brookings Institution Press, 2007)
"Through interviews, gives a behind-the-scenes look at negotiations to denuclearize the Korean peninsula. Offering multiple perspectives on the second Korean nuclear crisis, provides a window of understanding on the historical, geopolitical, and security concerns at play on the peninsula since 2002, paying special attention to China's dealings with North Korea"--Provided by publisher